A Pilot Study on Secondhand Smoke Exposure Among Pregnant Women in Chongqing, China: A Combined Questionnaire, Saliva Cotinine Test, and Ultrasound Flow Index Analysis - Tang, Jing; Shen, Jie; Zhang, Shengjie; Ho, Harvey; Ran, Suzhen (Frontiers in Public Health, 2020)
Objective: The aim of the study was to gain updated data on SHS exposure among pregnant women in Chongqing city, one of the four municipalities of China. Study Design and Setting: Pregnant women attending routine ultrasound checks at an obstetrics and gynecology center voluntarily participated in the survey of SHS exposure. Some participants were also invited to have saliva cotinine tests using a NicAlert kit. The pulsatility index (PI) of the umbilical artery was compared between the SHS and non-SHS groups. Results: A total of 548 pregnant women (74.82 and 25.18% at 12 and 24 weeks' gestation, respectively) participated in the survey from July to November 2019. SHS exposure was reported by 29.44% of participants. “Workplace” was listed as the top location for SHS exposure. Twenty-three of the 31 participants who tested cotinine-negative in their saliva samples self-reported SHS exposure in the survey questionnaire. However, two of the eight participants who tested cotinine-positive in their saliva samples self-reported SHS-exposure negative. The mean PI in the SHS group is higher than that in the non-SHS group (1.10 vs. 1.02) in fetuses at 24 weeks' gestation. However, the PI may not be suitable as an index for SHS exposure at 12 weeks' gestation due to frequent absent or reversed diastolic flow. Conclusion: The first survey on SHS exposure in pregnant women that combines a questionnaire, saliva cotinine tests, and ultrasound flow index analysis has been performed in China and provided valuable data for ensuing studies.